2020
DOI: 10.22225/seas.4.2.2291.95-101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biochar and Compost from Chicken, Goat, and Cow Manure on Cultivation of Red Chili (Capsicum annuum L)

Abstract: Abstract   This study aims to determine the effect of compost and biochar fertilizer at a dose of 15 tons ha-1 made from livestock manure and its interaction on the growth and yield of red chili plants. This research was conducted in Blahkiuh Village, Abiansemal District, Badung Regency, Bali with an altitude of 400-500 m above sea level. This research was started from February 2020 to July 2020. The design used in this study was a factorial randomized block design (RBD) consisting of 2 factors, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…The raw materials for making compost and biochar generally come from agricultural waste and livestock manure, which is very abundant, but this waste has not been used properly. Several studies have shown the positive effect of applying 10-15 tons/ha of biochar and compost from livestock manure on increasing soil fertility and chili yields [14,15].…”
Section: Research Backgroundmentioning
confidence: 99%
“…The raw materials for making compost and biochar generally come from agricultural waste and livestock manure, which is very abundant, but this waste has not been used properly. Several studies have shown the positive effect of applying 10-15 tons/ha of biochar and compost from livestock manure on increasing soil fertility and chili yields [14,15].…”
Section: Research Backgroundmentioning
confidence: 99%
“…Hasil serupa juga diperoleh (Hapsoh et al, 2019) bahwa peningkatan pupuk NPK hingga 250 kg ha -1 di samping pupuk kompos pada tanaman cabai merah masih meningkatkan bobot buah per tanaman. Penggunaan pupuk kandang ayam juga memberikan sumbangan akan keunggulan Paket-C. Pada cabai merah, penggunaan pupuk kandang kotoran ayam memberikan hasil yang lebih tinggi dibandingkan pupuk kotoran sapi (Adhikari et al, 2016;Mahendra et al, 2020), sebagai akibat kandungan unsur hara makro pupuk kandang ayam yang lebih baik dibandingkan pupuk kandang sapi (Masriyana et al, 2020).…”
Section: Hasil Dan Pembahasanunclassified
“…Manure is a waste product from domestic animals such as chickens, goats, and cows which can attach nutrients and raise the physical and biological soil properties. Manure quality can influence plants' response [10]. The benefit of applying manure on yield is increased soil organic carbon storage, soil nutrient content, and pH [11].…”
Section: Introductionmentioning
confidence: 99%
“…Compost is the product of converting diverse types of organic matter, such as leaves, grass, and straw, by weathering into compost with the help of microbes. Compost can advance soil fertility and available nutrient for plants due to its relatively stable decomposed organic materials [10]…”
Section: Introductionmentioning
confidence: 99%